Basic and applied biology of the photosynthetic flatworm Symsagittifera roscoffensis - NATHAN THOMAS (2024)
Photosymbiosis exists in both terrestrial and aquatic environments. Photosymbionts within a marine setting, utilising a photosynthetic partner, such as algae, provide photoassimilates to the host via photosynthesis. An example of this is photosymbiosis between Symsagittifera roscoffensis and the alga Tetraselmis convolutae. The host (S. roscoffensis) is entirely dependent on the alga for its nutrition to the extent that the host becomes photoautotrophic. Symsagittifera roscoffensis inhabits the dynamic intertidal zone along the Atlantic coast, adapting to conditions and light availability while minimizing dispersal. As this organism is found along the Atlantic coast and has limited swimming ability, thus giving rise to an unclear intra-species genetic diversity. To enhance understanding of how environmental conditions affect the worms, in Chapter 2, I examined the impact of changing abiotic factors on the symbiont’s photosynthesis.alinity (20, 30, 40) and nutrient (f/8, f/4, f/2), showed no significant effect, while increases in temperature, light intensity and photoperiod resulted in significantly lower photosynthesis.hese data are crucial for understanding how the symbiont provides photoassimilates in an ever-changing environment and in vitro culture optimization. Chapter 3; I explored S. roscoffensis’ behaviour responses to stimuli. Aposymbiotic juveniles displayed positive chemotaxis towards algae. Adults were able to balance light exposure and dispersal risk by repeated up and down movements. Worms avoided excessive light intensity by burrowing into the substrate. Mechanical vibrations triggered a downward movement above a threshold, below the threshold worms did not respond, allowing them to remain at the surface to continue photosynthesising These behaviours enable the S. roscoffensis to optimise photosynthesis while maintains its position within the intertidal zone. In Chapter 4; I analysed field conditions at East Aberthaw, Wales for 13 months and assessed genetic diversity among populations of S. roscoffensis and its symbiont T. convolutae from Wales, France, Guernsey, Spain and Portugal. Environmental changes, primarily temperature, influenced the size of the population at the local site. Limited gene flow between populations along the Atlantic coast was encountered; suggesting little migration, allowing populations to become locally adapted. Chapter 5; I used qPCR to quantify algal cells in juvenile and adult worms. Juveniles showed little difference in the algae cell’s numbers. While adult worms contained more algal cells than previously reported in the literature. Chapter 6; I investigated S. roscoffensis as an ornamental fish feed. Nutritional analysis showed essential polyunsaturated fatty acids, and feeding trials indicated palatability for both freshwater and marine species. Aposymbiotic juveniles formed symbiosis with other Tetraselmis species, suggesting a high level of plasticity with regards to the algal symbiont. This thesis represents a substantial knowledge gain regarding onS. roscoffensis and photosymbiosis, presenting insights into host-symbiont relationships and promoting its use as a model for further study in this field.